Affective performance and cognitive science : body, brain and being - Shaughnessy, Nicola; McConachie, Bruce A. (London : Methuen Drama, 2013)
This book explores new developments in the dialogues between science and theatre and offers an introduction to a fast-expanding area of research and practice.The cognitive revolution in the humanities is creating new insights into the audience experience, performance processes and training. Scientists are collaborating with artists to investigate how our brains and bodies engage with performance to create new understanding of perception, emotion, imagination and empathy. Divided into four parts, each introduced by an expert editorial from leading researchers in the field, this edited volume offers readers an understanding of some of the main areas of collaboration and research: 1. Dances with Science 2. Touching Texts and Embodied Performance 3. The Multimodal Actor 4. Affecting Audiences Throughout its history theatre has provided exciting and accessible stagings of science, while contemporary practitioners are increasingly working with scientific and medical material.
boek